The Ethical Climate of Danish Firms: A Discussion and Enhancement of the Ethical-Climate Model - Lemmergaard, Jeanette (Journal of business ethics, 2008)
The initial purpose of this study is to provide an empirical validation of Victor and Cullen’s ethical-climate model (1987, Frederick (ed.), Research in Corporate Social Performance and Policy, Vol. 9, pp. 51–71; 1988, Administrative Science Quarterly 33, 101–125; 1990, Frederick and Preston (eds.), Business Ethics: Research Issues and Empirical Studies (JAI Press Inc., Greenwich, Connecticut), pp. 77–97). Testing the model on a sample of Danish firms, this study demonstrates that the empirical model as suggested by Victor and Cullen is much stronger than suggested by previous research. Based on a confirmatory factor model, the results of this study suggest a revised ethical structure. Especially a sixth dimension – own interest – is separated from the original instrumental dimension. Further, this study suggests that the ethical-climate model can be enhanced with the dimension of autonomy deriving from Koys and DeCotiis’ (1991, Human Relations 44(3), 265–285.) dimensional psychological climate instrument.